Pengaruh Budaya Organisasi Terhadap Produktivitas Kerja Pegawai Pada Badan Pusat Statistik Kabupaten Hulu Sungai Utara - Akhmad Berkatillah; Ahmad Baihaqi; Erfan Maulana; Marisa (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: Every organization needs to pay attention and regulate the existence of its employees in an effort to improve good performance. Organizational culture is one of the factors that affect employee productivity. Study aims to determine whether there is a significant influence between organizational culture and employee work productivity at the Central Bureau of Statistics of Hulu Sungai Utara Regency, and to find out how much influence organizational culture has on work productivity at the Central Bureau of Statistics of Hulu Sungai Utara Regency. This research uses a quantitative approach with quantitative associative type. Data collection techniques used are observation, questionnaires, literature study and documentation. Sources of data were obtained from the results of questionnaires distributed to employees of the Central Bureau of Statistics of Hulu Sungai Utara Regency. Analyzing the data from the questionnaire results using the SPSS 23 computer program. The results of this study indicate that there is a significant influence between organizational culture on employee work productivity seen from the calculation of the determinant coefficient, which is 70%, the result of product moment correlation analysis is 0.835 compared to 0.3494. So r_count > r_table, therefore it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is a significant influence between organizational culture on employee productivity at the Central Bureau of Statistics of Hulu Sungai Utara Regency. The Central Agency of Statistics of Hulu Sungai Utara Regency is expected to improve organizational culture for better work productivity and create innovative ideas to achieve office goals. Besides, it is more assertive in giving sanctions if subordinates make mistakes so that it becomes a lesson for the next